Measuring Family Harmony of the Low-Socioeconomic Status Family: A Scoping Review - Rezky, Astalia; Marianty, Dewi; Fauziah, Nailul (Journal of Psychological Perspective, 2025)
Family harmony is a critical component of individual and societal well-being, yet families with low socioeconomic status (SES) often face structural challenges—such as financial hardship, limited access to education and healthcare, and chronic psychosocial stress—that disrupt relational stability. This scoping review aims to synthesize existing research on how family harmony is conceptualized and measured in low-SES contexts. Using the PRISMA framework, twenty peer-reviewed articles published between 2019 and 2024 were selected from four major academic databases. The review identifies four key indicators commonly used to assess family harmony in low-SES households: health, family dynamics, education, and communication. Despite the presence of these indicators, the findings highlight a lack of standardized and context-sensitive measurement instruments that reflect the lived realities of economically disadvantaged families. This review contributes to theoretical development by reinforcing the relevance of systems-based frameworks in understanding how external socioeconomic stressors influence internal family functioning. Practically, the findings offer guidance for developing culturally grounded assessment tools and designing targeted social interventions such as parenting education, economic empowerment programs, and digital platforms to strengthen family cohesion in vulnerable communities.